Experimental Characterization of A Load Sensor Based on Singlemode – Multimode – Singlemode (SMS) Fiber Structure with A Variation of The Number of Bends - Rionda Bramanta Kuntaraco; Agus Muhamad Hatta; Sekartedjo Koentjoro; Catur Arif Prastyanto; Insrasurya Budisatria Mochtar (IPTEK Journal of Proceedings Series, 2014)
A load sensor based on singlemode-multimode-singlemode (SMS) fiber structure is presented in this paper. An SMS fiber structure with core diameter of 50 µm and length of 30 cm of the multimode fiber (MMF) section was chosen as a sensor. The measurement principle of the sensor is based on change of SMS fiber structure power response due to the applied load. A fiber bending and load transmitting (FBLT) device is designed to appropiately bend the SMS fiber structure under applied load in order to make the SMS fiber structure work as a load sensor. The applied load can bend the SMS fiber structure and hence affect the multimode interference (MMI) pattern that occured in SMS fiber structure. The number of bends that occured on SMS fiber structure is determined by the pin number of FBLT device. Five variations of pin number at 3, 5, 7, 9 and 11 pins were chosen. The applied load was varied at 0 – 100 kg. From the experiments, it is found that the relative outpout power response of the sensor gave a specific MMI pattern for each pin number variation. The configuration of 3 pins on FBLT device has the best response as a load sensor with the sensitivity at 1.32 μW/kg and R2 at 0.9783 with the longest measurement range from 1.82 – 91.32 kg.